2019
DOI: 10.1002/rth2.12176
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an electronic medical record tool for early detection of deep vein thrombosis in the ambulatory oncology setting

Abstract: Background Venous thromboembolism ( VTE ) is a major cause of morbidity, mortality, and hospitalization in cancer patients. Objectives To evaluate the feasibility of an electronic alert to identify and screen at‐risk individuals and gather rates of early detection of deep vein thrombosis ( DVT ). Patients/Methods An alert was built into the electronic medical record based on a validated ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…While multiple studies have validated the KS as a predictive tool for chemotherapy-associated VTE, there are some studies that say otherwise [9,[14][15][16][17][18]. Our study validated KS in a community setting with a predominant elderly population and showed that high KS as well as intermediate KS was associated with increased odds of VTE but only high KS when compared to low KS was statistically significant (p=0.032).…”
Section: Discussionmentioning
confidence: 60%
“…While multiple studies have validated the KS as a predictive tool for chemotherapy-associated VTE, there are some studies that say otherwise [9,[14][15][16][17][18]. Our study validated KS in a community setting with a predominant elderly population and showed that high KS as well as intermediate KS was associated with increased odds of VTE but only high KS when compared to low KS was statistically significant (p=0.032).…”
Section: Discussionmentioning
confidence: 60%
“…На аутопсії, ознаки тромбоемболічних ускладнень виявляються майже у половини онкологічних пацієнтів, ТЕЛА є причиною смерті у 15% хворих, що страждають на онкопатологію [1]. У сучасних дослідженнях доведено, що онкологічне захворювання підвищує ризик тромбозу глибоких вен та ТЕЛА в 4-7 разів [2,3]. Характерною особливістю тромбоемболічних ускладнень у пацієнтів з онкологічними захворюваннями є те, що тромбоз глибоких вен та тромбофлебіт поверхневих вен нижніх кінцівок погано піддаються медикаментозному лікуванню, є причиною зниження ефективності та нерідко, припинення лікування основного захворювання [4,5,6].…”
Section: вступunclassified
“…A similar EMR tool was developed by investigators in the U.S. to identify high‐risk patients for early detection. To better comply with new guidelines, this tool is currently being refashioned to recommend prophylaxis [42]. Most recently, U.S. investigators developed and deployed a model of care for VTE prevention in an outpatient clinic that included nurses, advanced practice providers, pharmacists, hematologists, oncologists, and the EMR to increase compliance with guidelines [43].…”
Section: Primary Prevention Approachesmentioning
confidence: 99%